+0  
 

Best Answer 

 #2
avatar+18827 
+10

x + 2y - 6 = 0

$$x + 2y - 6 = 0\\
2y=-x+6\\
\boxed{y=f(x)=-\frac{1}{2}x+3}\\\\
\small{\text{
r = radius of the circle
}}\\
\small{\text{
$
x=f(x)=r
$
}}\\
\small{\text{
$
x=-\frac{1}{2}x+3
$
}}\\
\small{\text{$\frac{1}{2}x+x=3 $}}\\
\small{\text{$\frac{3}{2}x=3 $}}\\
\small{\text{$x=\frac{2}{3}*3=2$}}\\
\small{\text{$r=2$. The center of the circle is $(x_m,\ y_m) =\ ( 2,\ 2)$
}}\\
\small{\text{The equation of the circle is:
}}\\
\small{\text{
$
(x-x_m)^2+(y-y_m)^2=r^2 \qquad (x-2)^2+(y-2)^2=2^2
$
}}$$

heureka  Feb 3, 2015
Sort: 

2+0 Answers

 #1
avatar+80935 
+10

We're looking for a point on the line that is an equal distance to both axis..........thus, we're looking for a point such that x = y

So, we have

x + 2y - 6 = 0      let y = x

x + 2x - 6  = 0

3x - 6  = 0

3x = 6

x = 2

And by the same rationale, y= 2

Thus, our center is (2,2)   and the radius = 2

Here's a graph...

GRAPH

 

CPhill  Feb 3, 2015
 #2
avatar+18827 
+10
Best Answer

x + 2y - 6 = 0

$$x + 2y - 6 = 0\\
2y=-x+6\\
\boxed{y=f(x)=-\frac{1}{2}x+3}\\\\
\small{\text{
r = radius of the circle
}}\\
\small{\text{
$
x=f(x)=r
$
}}\\
\small{\text{
$
x=-\frac{1}{2}x+3
$
}}\\
\small{\text{$\frac{1}{2}x+x=3 $}}\\
\small{\text{$\frac{3}{2}x=3 $}}\\
\small{\text{$x=\frac{2}{3}*3=2$}}\\
\small{\text{$r=2$. The center of the circle is $(x_m,\ y_m) =\ ( 2,\ 2)$
}}\\
\small{\text{The equation of the circle is:
}}\\
\small{\text{
$
(x-x_m)^2+(y-y_m)^2=r^2 \qquad (x-2)^2+(y-2)^2=2^2
$
}}$$

heureka  Feb 3, 2015

22 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details